2003
DOI: 10.1002/cncr.11037
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of bone marrow levels of neurofibromatosis‐1 protein and ras oncogene mutations in patients with acute myeloid leukemia and myelodysplastic syndrome

Abstract: BACKGROUNDIt has been reported that point mutations of the ras gene occur frequently in acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). However, the prognostic significance of ras gene mutations in patients with these disorders has been a controversial issue. Although abnormalities in the neurofibromatosis 1 (NF1) gene, which is a gene involved in the ras pathway, have been observed frequently in patients with juvenile chronic myelogenous leukemia, the role of these abnormalities in adult pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Leukemias with NF1 mutations usually have a poor prognosis, and strikingly shorter complete remission durations have been noticed in AML patients bearing NF1 or RAS mutations. 5 Although the association between the ATP-binding cassette transporter MDR1/PGP and drug resistance in AML has been well documented, we found no detectable difference in the transcriptional level of Abcb1a, Abcb1b and Abcb4 between sensitive and resistant cells (data not shown). Instead, we found that the level of phosphorylated ERK was elevated in B106, B114 and B117 compared to other BXH-2 AML cell lines tested, but this is not the case for total ERK1/2, p21…”
contrasting
confidence: 51%
“…Leukemias with NF1 mutations usually have a poor prognosis, and strikingly shorter complete remission durations have been noticed in AML patients bearing NF1 or RAS mutations. 5 Although the association between the ATP-binding cassette transporter MDR1/PGP and drug resistance in AML has been well documented, we found no detectable difference in the transcriptional level of Abcb1a, Abcb1b and Abcb4 between sensitive and resistant cells (data not shown). Instead, we found that the level of phosphorylated ERK was elevated in B106, B114 and B117 compared to other BXH-2 AML cell lines tested, but this is not the case for total ERK1/2, p21…”
contrasting
confidence: 51%
“…44 Recently, it has been described that affected children with NF1 may develop myeloid malignancies after losing their wild-type NF1 allele due to interstitial uniparental disomy. 45 To date, mutations in NF1 have not been identified in adult patients with any myeloid disorders 46 but, it has been recently demonstrated that hemizygotic NF1 mice are more sensitized to carcinogenic stimuli, which result in hematological disorders independent of mutation of Trp53. 47 The NF1 gene has also been shown to be downregulated by the AML1-ETO fusion gene, which represses NF1 gene expression, resulting in RAS overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Co-expression and interaction of NUP98-HOX9 with Meis1 has been shown to accelerate disease progression. 113 Finally, patients exhibiting mutations in the Nf1 45,87,114 tumour suppressor gene with Ras mutations had markedly shorter complete remission durations, 107 through loss of functional regulation of Ras (p21 ras ) activation in response to GM-CSF. These examples accentuate the significance of transcriptional dysregulation and emphasise the importance of signalling pathways in human AML.…”
Section: Mulv Models Of Amlmentioning
confidence: 99%
“…There is substantial homology between the genes mutated and identified by proviral tagging in mouse AML and those implicated in the human disease [100][101][102][103][104][105][106][107][108] as exemplified in the following cases. Firstly, the AML1(Cbfa2, Runx1, Pebp2aB) 84 oncogene targeted by chromosomal translocation t (8;21), in approximately 12% of AML cases, 109 has been shown to play a vital role in the regulatory expression of many genes involved in haematopoietic cell development.…”
Section: Mulv Models Of Amlmentioning
confidence: 99%